2023
DOI: 10.1002/jper.22-0314
|View full text |Cite
|
Sign up to set email alerts
|

Salivary macrophage activation‐related chemokines and mitogen‐activated kinase kinase‐degrading proteolytic activity in type 1 diabetes mellitus

Abstract: Background This cross‐sectional study aimed to evaluate salivary concentrations of macrophage activation‐related chemokines and mitogen‐activated kinase kinase (MAPKK)‐degrading proteolytic activity in children and adolescents with and without type 1 diabetes mellitus (T1DM). Methods A total of 122 children and adolescents (65 T1DM patients, 50.8% female, mean age:10.9 years; 57 systemically healthy controls, 36.8% female, mean age: 9.5 years) were included in the study. Salivary concentrations of interferon g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…Furthermore, a case-control study revealed increased salivary IL-17 levels in diabetic children, highlighting potential immune dysregulation in T1DM (del Valle et al, 2015). Additionally, Yilmaz et al (2023) demonstrated altered salivary concentrations of macrophage activation-related chemokines and MAPKK-degrading proteolytic activity in T1DM patients showing higher levels of monokine induced by interferon gamma (MIG) and macrophage inflammatory protein-1 alpha (MIP-1α) in saliva of T1DM patients, underscoring the impact of T1DM on the host immune response (Yilmaz et al, 2023).…”
Section: Host Immune Markersmentioning
confidence: 99%
“…Furthermore, a case-control study revealed increased salivary IL-17 levels in diabetic children, highlighting potential immune dysregulation in T1DM (del Valle et al, 2015). Additionally, Yilmaz et al (2023) demonstrated altered salivary concentrations of macrophage activation-related chemokines and MAPKK-degrading proteolytic activity in T1DM patients showing higher levels of monokine induced by interferon gamma (MIG) and macrophage inflammatory protein-1 alpha (MIP-1α) in saliva of T1DM patients, underscoring the impact of T1DM on the host immune response (Yilmaz et al, 2023).…”
Section: Host Immune Markersmentioning
confidence: 99%
“…Cytokine analysis was performed as previously described [24,25]. In brief, saliva samples were thawed and centrifuged at 9300× g for 5 min at room temperature.…”
Section: Cytokine Analysismentioning
confidence: 99%
“…Salivary levels of interleukin (IL)-1β, IL-8, monocyte chemoattractant protein-1 (MCP-1), and macrophage migration inhibitory factor (MIF) were measured as previously described [15,16]. In brief, salivary samples were centrifuged at 9300× g for 10 min at room temperature.…”
Section: Cytokine Analysismentioning
confidence: 99%